A Replisome’s journey through the bacterial chromosome - Beattie, Thomas R.; Reyes-Lamothe, Rodrigo (Frontiers in Microbiology, 2015)
Genome duplication requires the coordinated activity of a multi-component machine, the replisome. In contrast to the background of metabolic diversity across the bacterial domain, the composition and architecture of the bacterial replisome seems to have suffered few changes during evolution. This immutability underlines the replisome’s efficiency in copying the genome. It also highlights the success of various strategies inherent to the replisome for responding to stress and avoiding problems during critical stages of DNA synthesis. Here we summarise current understanding of bacterial replisome architecture and highlight the known variations in different bacterial taxa. We then look at the mechanisms in place to ensure that the bacterial replisome is assembled appropriately on DNA, kept together during elongation, and disassembled upon termination. We put forward the idea that the architecture of the replisome may be more flexible that previously thought and speculate on elements of the replisome that maintain its stability to ensure a safe journey from origin to terminus.